State Support for Rebels and Interstate Bargaining - Qiu, Xiaoyan (Christy) (John Wiley and Sons Inc, 2022)
Since the end of World War II,leaders have frequently supported rebel groups in other countries as a coercive strategy in international disputes. However,the strategic rationale by which rebel groups gain international support is non-obvious. Many recipient groups are too weak to viably win and are hostile to the sponsoring state's goals. Using a formal model,I explain that the fundamental objective of transnational rebel support is to gain bargaining leverage against a rival state by depleting its resources to counter internal and external challenges. This subversive effect provides a sufficient incentive for sponsoring the rebels even when favourable conditions suggested by previous studies are absent. Sponsoring rebels is attractive even if conventional warfare is not comparatively costly and even if rebel and sponsor preferences diverge. Moreover,given the goal of destabilizing rival regimes,potential sponsors prefer to support weaker rebel groups and provide more support to them. © 2022 The Authors. American Journal of Political Science published by Wiley Periodicals LLC on behalf of Midwest Political Science Association.
Keywords: 59 Ciencia Política::5901 Relaciones internacionales; ODS 16 - Paz, justicia e instituciones sólidas